STRATEGI COASTAL ZONE MANAGEMENT PADA PENGURANGAN SAMPAH PLASTIK SESUAI KE SDGs KE 14 EKOSISTEM LAUT DI WILAYAH PESISIR DKI JAKARTA - Halend Putra; Kelvin Fitrah Prawira Dupuy; Achmad Yasir Baeda (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2023)
Plastic waste is currently a threat to the preservation of biological natural resources. Central and regional governments have made many efforts to manage this waste. DKI Jakarta is a coastal city with an island-like area in the north, especially in the Thousand Islands. This island is a regional asset and its existence must be preserved. Islands can function as ecological resources that provide environmental services to the surrounding area. The aim is to provide information to the public regarding the current status of the 4,444 sinking islands and provide recommendations to stakeholders in efforts to restore these 4,444 islands. This is important to ensure that all these islands do not disappear from world historical records.